Malays consumer racism ethnocentrism and animosity - Abdul Latif, Samshul Amry (IIUM Press, International Islamic University Malaysia, 2017)
The purpose of this research is to examine the effects of three exogenous constructs; consumer racism, ethnic-based consumer ethnocentrism and ethnic-based consumer animosity towards Malay consumers' product judgement and willingness to buy Chinese products. First, this chapter discusses the results from the main samples and analyzes the relationship results between each exogenous and endogenous constructs. This is then followed with further discussion based on the heterogeneity characteristic of the samples particularly the rural versus urban factor. After that, the implication towards and real-world application is considered.